Tailoring the Wettability and Substrate Adherence of Thin Polymer Films with Surface-Segregating Bottlebrush Copolymer Additives - Laws, Travis S (Langmuir : the ACS journal of surfaces and colloids, 2023)
We developed "reactive" bottlebrush polymers based on styrene (S) and t-butyl acrylate (tBA) as additives for polystyrene (PS) coatings. The bottlebrush polymers spontaneously bloom to both the air and substrate interfaces during solution casting. While neat PS films are hydrophobic and poorly adhere to the native oxide on clean silicon wafers, the hydrophilicity and substrate adherence of bottlebrush-incorporating PS films can be tailored through the thermally activated deprotection of tBA to produce acrylic acid (AA) and acrylic anhydride (AH). A critical design parameter is the manner by which tBA is incorporated into the bottlebrush: When the bottlebrush side chains are copolymers of S and tBA, the extent of deprotection is extremely low, even after prolonged thermal annealing at elevated temperature. However, when the bottlebrush contains a mixture of poly(t-butyl acrylate) (PtBA) and PS side chains, nearly all tBA is converted to AA and AH. Consequently, using the "mixed-chain" bottlebrush design with thermal processing and appropriate conditioning, the water contact angle is reduced from over 90° on unmodified PS down to 75° on bottlebrush-incorporating PS films, and the substrate adherence is improved in proportion to the extent of tBA deprotection